2018
DOI: 10.1111/ejss.12534
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dominant controls on biochar decomposition using boosted regression trees

Abstract: Summary Extensive studies have been carried out to investigate the decomposition of biochar. Biochar properties, soil characteristics and incubation conditions are considered key factors that control the rate of biochar decomposition. However, the relative contributions of these factors to its decomposition remain unknown. Approximately 812 individual measurements of the rate of biochar decomposition were collected from 23 studies involving 13C or 14C isotope techniques to evaluate the effects of incubation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, there is a large difference between the assumption of stable carbon in LCA studies and the 3%/97% split noted by Wang and colleagues, which is based on a meta-analysis of field/laboratory experiments [20]. This may be due to a lack of compiled carbon stability data at the time of the LCA studies as the meta-analysis of biochar stability are from 2016 and 2018 [18,20] or to a choice of keeping conservative assumptions. Thers and colleagues [249] showed that carbon sequestration is increased at higher pyrolysis temperature by 10% from 400 • C to 800 • C.…”
Section: Life-cycle Assessment Of Biochar Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a large difference between the assumption of stable carbon in LCA studies and the 3%/97% split noted by Wang and colleagues, which is based on a meta-analysis of field/laboratory experiments [20]. This may be due to a lack of compiled carbon stability data at the time of the LCA studies as the meta-analysis of biochar stability are from 2016 and 2018 [18,20] or to a choice of keeping conservative assumptions. Thers and colleagues [249] showed that carbon sequestration is increased at higher pyrolysis temperature by 10% from 400 • C to 800 • C.…”
Section: Life-cycle Assessment Of Biochar Systemsmentioning
confidence: 99%
“…Biochar decomposition follows a two-pool behavior, with a labile fraction that is quickly degraded and a recalcitrant fraction respectively estimated at 3 and 97% in a meta-analysis [20]. Based on the meta-analysis [18], average decomposition rates of biochar quickly drop from 0.6433%/day to 0.0024%/day after one year, due to depletion of the labile pool and then slow degradation of the recalcitrant pool [18]. Table 2 presents key production parameters increasing biochar recalcitrance: pyrolysis time (>3 h) and temperature (>400 • C).…”
Section: Soil Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant aspect affecting the calculation of biochar degradation rates and its effect on soil organic matter, both in laboratory and field experiments, is the duration of the study (Chao et al, 2018). It has been observed that short-term trials result in lower biochar mean residence time (Leng et al, 2019a), due to the decomposition of the labile biochar fraction and an overestimation of the positive priming effect, which normally occurs in the first few months.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, field experiments are essential to understand the dynamics of biochar in soils. Yet, despite their importance, field scale experimental studies on soil biochar degradation are still scarce (Jones et al 2012;Gurwick et al 2013).Another relevant aspect affecting the calculation of biochar degradation rates and its effect on soil organic matter, both in laboratory and field experiments, is the duration of the study (Chao et al 2018). It has been observed that short term trials result in lower biochar mean residence time (Leng et al 2019a), due to the decomposition of the labile biochar fraction, and an overestimation of the positive priming effect, which normally occurs in the first few months.…”
mentioning
confidence: 99%